Hubungan Metilasi DNA dengan Ekspresi Gen MADS-box pada Buah Mantel Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) - Anischan, Maharani; ,, Suharsono; Mathius, Nurita Toruan-; Kusnandar, Andree Sunanjaya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACT The presence of mantled fruit on large-scale clonal production of oil palm had trully decreased the oil productivity. Mantled phenotype is likely to be that of an epigenetic change involving DNA methylation and the MADS-box transcription factor gene which encoded floral organ homeotic transformation. The objectives of this research were to quantify the degree of methylation which determined fruit abnormality through Ultra Performance Liquid Chromatography (UPLC) and to study its correlation with the MADS-box EgAGL6, EgAG2, and EgAGA genes expressed on mantled fruit derived from oil palm clonal plants which have been quantified using Quantitative Real-Time PCR (qPCR). This research was arranged in two replications for each gene and cDNA. The expression of the target genes were compared to EF1-α1 as the reference gene. Through the Least Significant Difference (LSD) Test at 95% confidence level of qPCR result, EgAGL6 expression was significantly lower in mantled fruit which decreased from 1.88 fold in Abn m to 0.46 fold in Abn. EgAG2 expression was increased non-significantly from 0.91 fold in Abn m to 1.13 fold in Abn, while EgAGA expression was higher in mantled which increased significantly from 1.48 fold in Abn m to 1.71 fold  in Abn. Nuclease S1 digestion and UPLC revealed the genome-wide increase in DNA methylation on mantled fruit (18.33-19.55%) compared to its normal counterparts (5.67%). This increased in global DNA methylation was showed by the significant decreased in EgAGL6 transcript level of mantled fruit. This gene assumed to be involved in the development of mantled fruit. Keywords: DNA-methylation, MADS-box genes, Mantled fruit, Quantitative Real-Time PCR